2016
DOI: 10.1111/jmg.12179
|View full text |Cite
|
Sign up to set email alerts
|

Shooting at a moving target: phase equilibria modelling of high‐temperature metamorphism

Abstract: Thermodynamic modelling and calculation of P–T pseudosections are commonly employed for quantifying the P–T evolution of metamorphic rocks. A key assumption involved in interpreting a P–T pseudosection is that the bulk‐rock composition used is representative of the effective bulk composition (EBC) from which apparently equilibrated mineral assemblages grew. Choosing an EBC can be difficult in cases where the rock has evolved significantly throughout the P–T history and has become domainal for whatever reason (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 85 publications
(171 reference statements)
2
72
0
Order By: Relevance
“…We note, however, that tight clockwise P–T paths characterized by limited HT decompression (~1 kbar or less) have been inferred from various settings interpreted to result from orogenic processes (e.g. Armstrong, Tracy, & Hames, ; Attoh, ; Buick, Cartwright, & Harley, ; Couëslan & Pattison, ; Diener, White, Link, Dreyer, & Moodley, ; Guevara & Caddick, ; Johnson, Clark, Taylor, Santosh, & Collins, ; Williams & Karlstrom, ), including low‐ P migmatites from the Himalaya (Groppo, Rolfo, & Mosca, ).…”
Section: Potential Mechanisms For Ht Metamorphismmentioning
confidence: 73%
See 1 more Smart Citation
“…We note, however, that tight clockwise P–T paths characterized by limited HT decompression (~1 kbar or less) have been inferred from various settings interpreted to result from orogenic processes (e.g. Armstrong, Tracy, & Hames, ; Attoh, ; Buick, Cartwright, & Harley, ; Couëslan & Pattison, ; Diener, White, Link, Dreyer, & Moodley, ; Guevara & Caddick, ; Johnson, Clark, Taylor, Santosh, & Collins, ; Williams & Karlstrom, ), including low‐ P migmatites from the Himalaya (Groppo, Rolfo, & Mosca, ).…”
Section: Potential Mechanisms For Ht Metamorphismmentioning
confidence: 73%
“…Carlson, ), with several studies highlighting the utility of domainal compositions of individual mm‐scale microstructures in phase equilibria modelling of residual HT metamorphic rocks (e.g. Anderson, Kelsey, Hand, & Collins, ; Baldwin, Powell, Brown, Moraes, & Fuck, ; Guevara & Caddick, ; Johnson, Brown, Gibson, & Wing, ; Nasipuri, Bhattacharya, & Das, ; White et al., , ). We did not use domainal compositions for phase equilibria modelling here, instead choosing to use bulk‐rock compositions determined by XRF because: (1) garnet porphyroblasts up to 3 cm apart in sample BHP13‐03D have similar chemical zonation, interpreted to record similar growth histories and suggesting that equilibrium length‐scales during garnet growth were likely at the cm‐scale, (2) petrographic observations in both samples suggest that melt was present on grain boundaries before and during cooling, which probably helped to facilitate equilibration over such length‐scales, and (3) the rocks do not display any microstructures suggestive of diminished equilibrium length‐scales at HT conditions (e.g.…”
Section: Phase Equilibria Modellingmentioning
confidence: 99%
“…varying mineral abundances) between the sample and thin section (Palin, Weller, Waters, & Dyck, ). Another is that determining the appropriate equilibration volume and therefore the effective bulk composition in high‐grade rocks is difficult, as it is likely to vary throughout the metamorphic evolution as a result of melt loss, changing temperature and different diffusion rates of elements (Guevara & Caddick, ; Kelsey & Hand, ). These factors may result in a mismatch between the mineral proportions observed in a 2D thin section and those present in the 3D, hand sample‐sized volume used for XRF analysis.…”
Section: Resultsmentioning
confidence: 99%
“…() demonstrated that equilibrium partial melting failed to explain the formation of K 2 O‐poor leucosomes at peak metamorphic conditions (~875°C and ~11 kbar). Guevara and Caddick () showed that P–T estimates via phase equilibrium modelling are highly dependent on the volume of rock considered to represent the equilibration volume. Green et al.…”
Section: Discussionmentioning
confidence: 99%